Impact of visceral obesity and sarcobesity on surgical outcomes and recovery after laparoscopic resection for colorectal cancer. Issue 12 (December 2020) - Pedrazzani, C.; Conti, C.; Zamboni, G.A.; Chincarini, M.; Turri, G.; Valdegamberi, A.; Guglielmi, A.
Summary: Background & aims: Studies analyzing the impact of visceral fat excess on surgical outcomes after resection for colorectal cancer (CRC) have yielded conflicting results. Visceral obesity (VO) and sarcobesity (SO) have been recently addressed as risk factors for poor short-term results while no data are available for recovery goals after surgery. No data are available on the protective effect of ERAS in VO and SO patients. The aim of this study was to assess clinical implications of computed tomography (CT) assessed VO and SO on surgical and recovery outcomes after minimally invasive resection for CRC before and after ERAS protocol implementation. Methods: Visceral adipose tissue (VAT) and skeletal muscle area (SMA) were retrospectively assessed using pre-operative CT studies of 261 patients who underwent laparoscopic resection for CRC between January 2012 and April 2019; ERAS protocol was adopted in 160 patients operated on after March 2014. Patients' surgical and recovery outcomes were compared according to BMI categories, VO and SO which was defined using the VAT/SMA ratio (Sarcobesity Index). Predictive factors for poor surgical and recovery outcomes were evaluated by univariate and multivariate analyses. Results: Of the 261 patients, 12.6% were BMI obese while 68.6% presented visceral obesity. BMI was not associated to any of the outcomes considered. No differences in intra-operative results were found except for a lower number of retrieved lymph nodes both in VO and SO patients. While VO showed no impact on post-operative course, SO resulted an independent risk factor for cardiac complications and prolonged post-operative ileus (PPOI) at logistic regression analysis. Furthermore, sarcobese patients showed delayed recovery after surgery. Patients enrolled in the ERAS protocol showed improved recovery outcomes for both VO and SO groups, although ERAS did not result to be a protective factor for cardiac complications and PPOI. Conclusions: A high Sarcobesity Index is a risk factor for developing cardiac complications and PPOI after laparoscopic resection for CRC. A reduced number of lymph nodes retrieved is associated to VO and SO. These conditions should then be considered in clinical practice for the risk of down staging the N stage. Effect of VO and SO on recovery items after surgery should be further investigated. ERAS protocol application should be implemented to improve recovery outcomes in VO and SO patients undergoing laparoscopic colorectal resection.